Where Have You Been Hiding? Re-Emergence of Squatina oculata in the Sea of Marmara, with a Review of Captures in Turkish Seas - F. Saadet Karakulak; Uğur Uzer; Hakan Kabasakal (Aquatic Sciences and Engineering)
On February 27, 2018, a female smoothback angelshark, Squatina oculata, was incidentally captured in a gill-net fishery off the Mudanya coast (southeastern Sea of Marmara). An opportunistic photographic record confirmed the emergence of S. oculata in the Sea of Marmara, where its status in the area is considered questionable because of its absence for many years in the region. The current opportunistic records are valuable data sources, which can provide complementary information to fill the knowledge gaps in the life histories of rare, rarely caught, or endangered sharks and rays.